2020
DOI: 10.1172/jci134091
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 and immunologically induced senescence regulate response to injury in osteoarthritis

Abstract: Conflict of interest: DZ is an inventor of a pending patent application for BCL-xL inhibitors and targeted senolytic agents for age-related diseases (Compounds that induce degradation of anti-apoptotic BCL-2 family proteins and the uses thereof, no. US20190135801). DZ and JC are cofounders, advisors for, and shareholders of Unity Biotechnology, which develops senolytic agents. JHE is an equity holder of Unity Biotechnology, receives patent royalties through Johns Hopkins University School of Medicine (Unit dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
124
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(126 citation statements)
references
References 77 publications
2
124
0
Order By: Relevance
“…These studies demonstrate that, like TNF-α or IL-β, IL-17 is strongly capable of enhancing inflammation and causing catabolic effects that lead to degeneration of articular cartilage; and that potentiating effects of cytokine combinations with IL-17 surpass those of individual cytokines. This review, in the context of PTOA of the knee, as well as others reviews, suggest that IL-17 is a crucial pathogenic molecule in local and systemic disease pathogenesis in many types of disease tissues and that IL-17 signaling may promote chronic disease development [ 185 , 186 , 187 , 188 , 189 ] emphasizing the need for further mechanistic IL-17 studies in various contexts.…”
Section: Results Of the In Vivo Ex Vivo And In Vitro Models That mentioning
confidence: 95%
See 3 more Smart Citations
“…These studies demonstrate that, like TNF-α or IL-β, IL-17 is strongly capable of enhancing inflammation and causing catabolic effects that lead to degeneration of articular cartilage; and that potentiating effects of cytokine combinations with IL-17 surpass those of individual cytokines. This review, in the context of PTOA of the knee, as well as others reviews, suggest that IL-17 is a crucial pathogenic molecule in local and systemic disease pathogenesis in many types of disease tissues and that IL-17 signaling may promote chronic disease development [ 185 , 186 , 187 , 188 , 189 ] emphasizing the need for further mechanistic IL-17 studies in various contexts.…”
Section: Results Of the In Vivo Ex Vivo And In Vitro Models That mentioning
confidence: 95%
“…DAMPs are present in normal healthy chondrocytes, but increased in OA [ 260 ]. DAMPs also induce cellular senescence and are produced by senescent cells (SnCs) and, like DAMPs, cellular senescence has been suggested to contribute to low grade chronic systemic inflammation in OA [ 261 , 262 , 263 ] and in PTOA [ 189 , 264 , 265 , 266 ]. Senescent cells (SnCs) increase in response to aging but also increase upon injury, stress and inflammation and, thus, are relevant to trauma-related pathologies.…”
Section: Summary Outlook and Early Disease Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, IL-17 inhibition appears to be effective in the treatment of psoriasis (43). Notably, a recent study revealed that intra-articular injection of an IL-17-neutralizing antibody reduced joint degeneration in aging OA mice (44). However, IL-17 inhibition has not been trialed in the treatment of OA in patients.…”
Section: Discussionmentioning
confidence: 99%